2019
DOI: 10.3389/fmed.2019.00283
|View full text |Cite
|
Sign up to set email alerts
|

The General Symptom Questionnaire-30 (GSQ-30): A Brief Measure of Multi-System Symptom Burden in Lyme Disease

Abstract: Introduction: The multi-system symptoms accompanying acute and post-treatment Lyme disease syndrome pose a challenge for time-limited assessment. The General Symptom Questionnaire (GSQ-30) was developed to fill the need for a brief patient-reported measure of multi-system symptom burden. In this study we assess the psychometric properties and sensitivity to change of the GSQ-30.Materials and Methods: 342 adult participants comprised 4 diagnostic groups: Lyme disease (post-treatment Lyme disease syndrome, n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 28 publications
2
27
1
Order By: Relevance
“…The prolonged, subjective symptoms frequently reported in the context of Lyme disease (e.g., fatigue, widespread pain, cognitive complaints, paresthesia, and sleep disruption) also broadly represent those commonly reported in outpatient settings (72)(73)(74). Furthermore, while some differences in impairment and symptom distribution have been studied and reported (75)(76)(77), there is also a degree of general symptom overlap with other disease states such as traumatic brain injury, depression, chronic fatigue syndrome, and fibromyalgia (78). This lack of sensitivity can lead to the conclusion that the prolonged symptoms reported in Lyme disease are no different than the "background noise" of symptoms in the general population.…”
Section: Symptomsmentioning
confidence: 92%
“…The prolonged, subjective symptoms frequently reported in the context of Lyme disease (e.g., fatigue, widespread pain, cognitive complaints, paresthesia, and sleep disruption) also broadly represent those commonly reported in outpatient settings (72)(73)(74). Furthermore, while some differences in impairment and symptom distribution have been studied and reported (75)(76)(77), there is also a degree of general symptom overlap with other disease states such as traumatic brain injury, depression, chronic fatigue syndrome, and fibromyalgia (78). This lack of sensitivity can lead to the conclusion that the prolonged symptoms reported in Lyme disease are no different than the "background noise" of symptoms in the general population.…”
Section: Symptomsmentioning
confidence: 92%
“…Recently, another instrument was developed to assess and track the burden of multi-system symptoms associated with LD. Although it does not purport to be a primary diagnostic aid, and cannot distinguish between PTLDS and traumatic brain injury or depression, the General Symptom Questionnaire-30 (GSQ-30) is positioned as a monitoring tool for clinical and research use [75]. The GSQ-30 evaluates four domains relevant to LD (pain/fatigue, neuropsychiatric, neurologic, and viral-like symptoms), and is sensitive to changes in the patient's wellbeing over the course of treatment.…”
Section: Classifying Lyme Diseasementioning
confidence: 99%
“…Furthermore, a pilot study used [ 11 C]DPA-713 PET imaging to study cerebral glial activation and found that several brain regions had higher [ 11 C]DPA-713 binding in patients with PTLDS than in healthy controls (12). In addition to these biomarkers, Fallon et al (69) developed a survey, the General Symptom Questionnaire-30 (GSQ-30), to assess symptom burden and changes; patients with PTLDS reported higher GSQ-30 scores before treatment and maintained these scores until 6 months posttreatment. The GSQ-30 could be a powerful tool to accompany biomarkers like the gut microbiome in PTLDS.…”
Section: Discussionmentioning
confidence: 99%